Revision of the genus Metaterpna Yazaki, 1992 (Lepidoptera, Geometridae, Geometrinae), with description of a new species from China - Jiang, Nan; Stüning, Dieter; Xue, Dayong; Han, Hongxiang (Zootaxa, 2016)
The genus Metaterpna is revised. The two species known, M. differens (Warren, 1909) and M. thyatiraria (Oberthür, 1913), are redescribed, with emphasis on the considerable variability of M. thyatiraria, and the status of the related type specimen was discussed. In addition, one new species, M. batangensis sp. nov., is described from Batang and Daocheng, Sichuan province, and Lijiang, Yunnan province, southwestern China. M. thyatiraria and M. batangensis show clear distance by DNA barcode sequences. Illustrations of moths and genitalia are presented.